Fiber arts and generative justice - Kuhn, Sarah (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2016)
The fiber arts, because they are practiced in different forms around the globe, have the potential to teach us much about generative justice that unites labor, ecological, and expressive values. The ecological mutualism documented in Navajo corrals supports traditional weaving, dyeing, food, and medicinal practices in a sustainable and generative cycle that survives despite disruption and exploitation. The network of fiber craftspeople, retailers, ranchers, teachers, spinners, and dyers and their organizations supports the social mutualism of fiber communities. Fiber arts practices can benefit individuals, communities, the environment, and public health, among other things. Conscious fiber activism and critical making can also be used to explicitly draw attention to problems such as overconsumption, waste, industrial “fast fashion,” labor exploitation, environmental degradation, toxic risks, intolerance, and the devaluing of women and their work. Fiber arts have the potential to support environmental and social mutualism and catalyze a new aesthetic of long-term attachment to meaningful objects and communities, reinforcing the creation and conservation of expressive, ecological, and labor value.